PEDAGOGICAL DEONTOLOGY HAS TAKEN HOLD OF COMMUNICATION CULTURE OF TECHNICAL HIGHER EDUCATION STUDENTS FROM THE BEGINNING (American Journal of Interdisciplinary Research and Development, 2024)
This article delves into the profound influence of pedagogical deontology on the communication culture of technical higher education students. From the inception of their academic journey, students are immersed in a dynamic environment where ethical principles guide both teaching methodologies and interpersonal interactions. The exploration begins by establishing the ethical foundations within technical education, emphasizing integrity, transparency, and accountability. As students progress, the article examines how pedagogical deontology shapes a collaborative and respectful classroom environment, fostering communication skills crucial for their professional development. The integration of ethical communication practices in technical projects and assignments is explored, highlighting the ethical considerations required for successful execution. The article concludes by emphasizing the enduring impact of pedagogical deontology on professionalism and ethical communication skills as students transition into the professional realm. Additionally, it addresses the adaptation of pedagogical deontology to technological advancements, ensuring ethical considerations persist in virtual communication spaces.